Devolved school-based financial management in New Zealand : observations on the conformity patterns of school organisations to change - Tooley, S.; Guthrie, J. (Massey University, 2003)
This paper examines the intent and consequences of ‘new’ financial management (the ‘New Public Financial Management’) (NPFM) procedures invoked to facilitate a macro-micro interface within the context of the significant administrative reform of the New Zealand (NZ) state education system. The 1989 administrative reform of the NZ education system was predicated on a particular view of public sector management, which was characterised by the umbrella heading of ‘New Public Management’ (NPM). It was claimed that NPFM provided a link between the sets of values highlighted through the NPM reform process and the internal workings of various public sector organisations. The study provides case studies of the organisational financial management practices of four schools, some ten years after the reform. The observed practices are analysed and interpreted within a theoretical framework comprising two competing theories of change – NPM which provides the ‘normative’ intent for public sector organisational change, and institutional theory that offers an explanation of the ‘operational’ consequences of public sector organisational (i.e. schools) response to change. The findings suggest that accounting and management technologies have served a useful, political purpose, although not in the way espoused by NPM proponents.
Keywords: Financial management; School finances; Organisational change; New Zealand education